1991
DOI: 10.1128/mcb.11.12.6279
|View full text |Cite
|
Sign up to set email alerts
|

Human c-fgr induces a monocyte-specific enzyme in NIH 3T3 cells.

Abstract: The mutant c-fgr protein (p58c-fgr/F523) containing Phe-523 instead of Tyr-523 exhibited transforming activity in NIH 3T3 cells like other protein-tyrosine kinases of the src family, but normal p58c-fgr (p5gc-fgIw't) did not.The mutant protein showed tyrosine kinase activity threefold higher than that of the normal protein in vitro. 58-, 62-, 75-, 120-, 200-, and 230-kDa proteins were commonly phosphorylated at tyrosine residues in NIH 3T3 cells transfected with normal and mutated c-fgr, while 95-kDa protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…This fact suggests that the physiological role of Fgr is associated with functions in differentiated cells. Indeed, we previously found that Fgr induced a monocyte-specific enzyme, NaF-sensitive a-naphthyl butyrate esterase, in NIH 3T3 mouse cells (30). In the present study, we have found that Fgr is associated with and comodulated with Fc4Il and is activated after receptor engagement with specific mAbs or natural ligands such as heat-aggregated human IgG, suggesting that Fgr is physically and functionally associated with FcRII in neutrophils.…”
supporting
confidence: 66%
“…This fact suggests that the physiological role of Fgr is associated with functions in differentiated cells. Indeed, we previously found that Fgr induced a monocyte-specific enzyme, NaF-sensitive a-naphthyl butyrate esterase, in NIH 3T3 mouse cells (30). In the present study, we have found that Fgr is associated with and comodulated with Fc4Il and is activated after receptor engagement with specific mAbs or natural ligands such as heat-aggregated human IgG, suggesting that Fgr is physically and functionally associated with FcRII in neutrophils.…”
supporting
confidence: 66%